Effect of bath temperature on the chemical bath deposition of PbSe thin films - Kassim, Anuar; Tee, Tan Wee; Min, Ho Soon; Monohorn, Shanthi; Nagalingam, Saravanan (Kathmandu University Journal of Science, Engineering and Technology, 2010)
PbSe thin films are prepared by chemical bath deposition technique over microscope glass substrates from an aqueous acidic bath containing lead nitrate and sodium selenate. The influence of bath temperature on the properties of PbSe film is investigated. The X-ray diffraction analysis showed the deposited films were polycrystalline and having the (111) orientation. The surface morphology study revealed that the grains have cubic shape crystal. The band gap energy was decreased from 2.0 to 1.3 eV as the bath temperature was increased from 40 to 80°C. The films deposited at 80°C showed good crystallinity and uniformly distributed over the surface of substrate with larger grain sizes. Therefore, the optimum bath temperature is 80°C. Keywords: Lead selenide; X-ray diffraction; Band gap energy; Chemical bath deposition; Thin films DOI: 10.3126/kuset.v6i2.4021 Kathmandu University Journal of Science, Engineering and Technology Vol.6. No II, November, 2010, pp.126-132